P52 Exploring the interaction between hiv-1 gp120, bronchial airway epithelial cells and macrophages. (15th November 2017) - Talbot, B; Stokes, CA; Collini, PJ; Condliffe, AM
Abstract : Rationale and Hypothesis: HIV-1-seropositive individuals receiving highly active antiretroviral therapy (HAART) have an increased incidence of chronic obstructive pulmonary disease (COPD), independent of smoking history. Although HIV-1 infection is associated with impaired redox homeostasis and increased pro-inflammatory cytokine expression in the lungs despite HAART, the mechanisms driving HIV-1-associated COPD are poorly understood. Free HIV-1 envelope glycoprotein gp120 is detectable in bronchoalveolar lavage fluid from HAART-treated individuals. gp120 displays affinity (tropism) for either CCR5 or CXCR4 chemokine receptors, and has been implicated as a mediator of inflammation and oxidative stress in various HIV-1-associated disease processes. We hypothesised that gp120 directly induces bronchial epithelial cell oxidative stress, and drives airway inflammation indirectly via alveolar macrophages, a response which is augmented following secondary exposure to pro-inflammatory stimuli such as bacterial pathogens. Objectives: To explore the mechanisms and consequences of gp120 interactions with bronchial epithelial cells and macrophages. Methods: An immortalised bronchial epithelial cell line (BEAS-2B), primary bronchial epithelial cells (PBECs) or monocyte-derived macrophages (MDMs) from healthy volunteers were treated with recombinant gp120 (CCR5- or CXCR4-tropic, 100 ng/mL) for 24–48 hour. BEAS-2B were primed (or not) with IL-1β. MDMs were co-cultured with confluent BEAS-2B cells at a ratio of 1:5 in the presence or absence of LPS (100 ng/ml). Cytokine outputs were quantified by ELISA, and cellular reactive oxygen species (ROS) production assessed by confocal microscopy using CellROX or MitoSOX reagents. Findings: Picomolar concentrations of CXCR4- but not CCR5-tropic gp120 induced CXCL8 release from IL-1β-primed BEAS-2B monocultures and upregulated cellular ROS production in both BEAS-2Bs and PBECs, consistent with expression of CXCR4 but not CCR5 on these cells. gp120 stimulation of BEAS-2B/MDM co-cultures caused no detectable changes in cytokine release. However, co-cultures primed with gp120 (of either tropism) and stimulated with LPS demonstrated significant CXCL8 release at 48 hours, reflecting MDM expression of both chemokine receptors. Impaired redox homeostasis and upregulated inflammatory responses may contribute to gp120-mediated airway epithelial dysfunction, and may drive neutrophil recruitment in this setting. Conclusion: HIV-1 gp120 influences key airway cell interactions to disturb redox homeostasis and inflammatory responses at concentrations equivalent to those found in the lungs of individuals receiving long-term HAART.